Prevalence, Forms, and Role Overlap of Cyberbullying Among Students at a Public Elementary School in Pekanbaru - Dede Suhada; Sigit Nugroho; Lisfarika Napitupulu; Irfani Rizal (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The increasing number of children actively using the internet nowadays raises concerns about their involvement in cyberbullying. However, the limited research on elementary school-aged children subjects poses an obstacle to implementing various actions such as prevention or intervention. The purpose of this research is to explore the prevalence and characteristics of cyberbullying in one of the elementary schools in Pekanbaru. This study employed a quantitative design by collecting data through distributing questionnaires. Involving 148 students from one of the elementary schools in Pekanbaru (M = 11 years, SD = 0.87). In data processing, the researcher used descriptive statistics. The results of this study indicate that approximately 46.7% (N=69) of students reported being victims of one or more forms of cyberbullying behavior, 29.7% (N=44) engaged in one or more forms of cyberbullying behavior, and 50.7% (N=75) witnessed one or more forms of cyberbullying behavior among their peers in the past six months. This study provides information on the prevalence, forms of behavior, roles, and patterns of internet use related to cyberbullying among students. Empirical evidence suggests considering preventive efforts in grades below grade VI, with the aim of preventing cyberbullying behavior before it becomes more frequent.